Effect of Fe0 particle size on buffering characteristics and biohydrogen production in high-load photo fermentation system of corn stover. (November 2022) - Zhu, Shengnan; Zhang, Yang; Zhang, Zhiping; Li, Yameng; Ai, Fuke; Zhang, Quanguo
Graphical abstract: Highlights: Fe 0 was first applied to high-load photo fermentation system of corn stover. Effects of Fe 0 sizes (700, 100 and 50 nm) on hydrogen production were compared. Fe 0 buffered pH, stimulated nitrogenase activity and accelerated acid utilization. Adding 1000 mg/L Fe 0 -700 obtained the highest hydrogen yield increment of 92.88 %. Abstract: The aim of this work was to study the effects of Fe 0 particle sizes (700 nm, 100 nm and 50 nm) addition on biohydrogen production, liquid culture characteristics and photosynthetic bacterial respond in the high-load photo fermentation system of corn stover within the concentration range of 200–1500 mg/L. Results showed that Fe 0 with particle size of 700 nm had a better promotion effect on hydrogen production than 100 nm and 50 nm. The highest hydrogen yield of 74.32 ± 3.48 mL/g TS and hydrogen production rate of 3.31 ± 0.11 mL/g·h TS corn stover were obtained at 1000 and 1500 mg/L Fe 0 -700 nm, which were significantly increased by 92.88 % and 133.88 % compared with the control group. Further analysis indicated that Fe 0 addition effectively alleviated pH drop, enhanced nitrogenase activity, promoted cell growth, and accelerated the consumption of acetic acid and butyric acid.